Study of timber and concrete with rubber waste composite beams applied to bridges - Pinheiro, Luís Henrique Bueno; Matthiesen, José Antônio [UNESP]; Akasaki, Jorge Luís [UNESP] (Trans Tech Publications, 2015)
In order to overcome the hydrographic network, the landforms, and the most different types of barriers, many timber bridges were constructed around the world, especially in secondary roads where the raw materials (wood) can be found in the vicinity, what reduces the construction costs. The deck can be made of reinforced concrete with the purpose of increasing the durability, strength and stiffness of these structures, and using rubber particles can not only decrease the costs and impact on the environment, but can also confer some advantages on the structure, such as a better impact absorption, and a lower cracking due to the abrasion wear, water absorption or self weight. The analysis of the bending behavior of these superstructures was performed through the study of ten mixed T section composite beams, with wooden web (mimicking the stringers) and a reinforced concrete top flange (mimicking the deck) with varying rubber waste percentage. Steel bars set to X, glued with epoxy resin on the wood, allowed the connection between wood and concrete, reducing manufacturing costs with high shear strength resistance. The constituent materials were characterized mechanically and the composite beams were equipped with a dial indicator and strain gauges, and then broken in flexure tests. At the same time, the rubber particles percentage was correlated with the following parameters: stress, strain, elasticity modulus, loads and displacements, what enabled us to find which rubber addition percentage was most adequate in order for this kind of structure to be in accordance with the project requirements for the resistance.
Keywords: Composite structures; Rubber in composite bridges; Timber-concrete composite beams